2016
DOI: 10.1007/s10661-016-5102-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of plant growth of two poplar tree species irrigated with treated wastewater, with particular reference to accumulation of heavy metals (Cd, Pb, As, and Ni)

Abstract: Water is a scarce natural resource around the world which can hamper the socio-economic development of many countries. The Mediterranean area, especially north Africa, is known for its semi-arid to arid climate, causing serious water supply problems. Treated wastewater (TWW) is being used as an alternative strategy for recycling wastewater. It is also a potential source of nutrients for reforestation with certain plant species such as poplar trees, a useful wood resource, and even for phytoremediation purposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 52 publications
0
13
1
1
Order By: Relevance
“…As the work of Tahriri Adabi et al (2013) showed high provided amount of water in 4 days interval in comparison to 8 and 12 days, make poplar species and clones more susceptible against pest. It is worth mentioning that today using treated wastewater for poplar irrigation is suggested as an alternative strategy for water supply problems in semi-arid to arid areas (Houda et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…As the work of Tahriri Adabi et al (2013) showed high provided amount of water in 4 days interval in comparison to 8 and 12 days, make poplar species and clones more susceptible against pest. It is worth mentioning that today using treated wastewater for poplar irrigation is suggested as an alternative strategy for water supply problems in semi-arid to arid areas (Houda et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“… 29 , 30 and Populus spp. 31 , were well adapted to SSC and were effective in taking up the heavy metals in sludge. These results suggested that selecting suitable woody plants that have high biomass and heavy metals tolerance can be an effective way to ensure the ecological safety of SSC utilization as soil amendments in landscaping.…”
Section: Introductionmentioning
confidence: 99%
“…In the natural environment, the half-life of benzene is 0.02-2 years; therefore, combined processes should be adopted, in different environmental compartments, to trigger biological degradation or even to contain benzene to vertically penetrate subsurface mobility and minimize negative impacts by means of various low-cost techniques (ASTM 1995). Thus, the use of plants as depollution agents has aroused increasing interest and has been evaluated mainly in soils contaminated with trace metals (Chowdhury et al 2015;Houda et al 2016;Kaewtubtim et al 2016), crude oil and its derivatives (Fatima et al 2016;Liao et al 2016), and other organic compounds (Ignatowicz 2016; Lafleur et al 2016). The use of plants that can tolerate and simultaneously extract toxic substances may offer an interesting alternative for in situ decontamination (Campos et al 2014).…”
Section: Resultsmentioning
confidence: 99%